2018
DOI: 10.1016/j.yebeh.2017.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Development and content validation of a preliminary core set of patient- and caregiver-relevant outcomes for inclusion in a potential composite endpoint for Dravet Syndrome

Abstract: This study showed the wider potential impact of DS to extend beyond that of seizures, demonstrating that there is a need for additional patient- and caregiver-relevant concepts to be measured in clinical trials to fully identify the value of therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 43 publications
(63 reference statements)
6
77
0
Order By: Relevance
“…12,14 These findings emphasize that a biopsychosocial approach to treatment should be developed for Dravet syndrome, with the implementation and evaluation of combined pharmacological and psychosocial interventions. impacts not directly attributable to the condition) to be as important as the direct impact of seizures, and that Dravet syndrome affected multiple domains of their lives.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…12,14 These findings emphasize that a biopsychosocial approach to treatment should be developed for Dravet syndrome, with the implementation and evaluation of combined pharmacological and psychosocial interventions. impacts not directly attributable to the condition) to be as important as the direct impact of seizures, and that Dravet syndrome affected multiple domains of their lives.…”
Section: Discussionmentioning
confidence: 97%
“…In the previous study by Nabbout et al 14 identified previously are still relevant and should be measured in future clinical trials on Dravet syndrome. A selected endpoint model must paint a comprehensive picture of the condition, incorporating aspects such as symptoms and the impact on the child and the caregiver.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations